Growth hormone and targeted oncological agents: Are we stopping children with brain tumours from reaching their true height potential?. (11th June 2021) - Walker, Hannah; Khuong Quang, Dong Anh; Campbell, Martin; Bhatia, Kanika; Williams, Molly; Sullivan, Michael; Eisenstat, David D; Kao, Kung‐Ting; Ng, Jessica; White, Mary; Zacharin, Margaret; Hansford, Jordan R
Abstract : Children with low‐grade gliomas have excellent long‐term survival outcomes. The development of therapies targeted to the driver mutations along the Mitogen Activated Protein (MAP) kinase signalling pathway are providing long‐term stability for many patients with these tumours. Given the frequency of these tumours residing within or near the suprasellar region, our patients commonly suffer from hormone deficiencies. In Australia, the Pharmaceutical Benefits Scheme currently restricts growth hormone therapy to patients who are not being actively treated for cancer, including those receiving targeted therapies. This viewpoint hopes to facilitate an important discussion amongst our colleagues as to whether this should be changed to allow growth hormone to become available to children on chronic tumour suppressive therapy.